Fourteenth Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems (ITherm) 2014
DOI: 10.1109/itherm.2014.6892316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of droplet diameter on the Leidenfrost temperature of laser processed multiscale structured surfaces

Abstract: In this paper, an experimental investigation of the effects of droplet diameters on the Leidenfrost temperature and its shifts has been carried out. Tests were conducted on a 304 stainless steel polished surface and a stainless steel surface which was processed by a femtosecond laser to form Above Surface Growth (ASG) nano/microstructures. To determine the Leidenfrost temperatures, the droplet lifetime method was employed for both the polished and processed surfaces. A precision dropper was used to vary the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…where is the evaporation time before correction; D0, present, the droplet diameter in this study; and D0, previous, the droplet diameter in previous studies. Figure 4 shows that the experimental results of the present study agree well with the results of previous studies near the LFP [16,27]. Comparison of evaporation time with those in previous studies [16,27].…”
Section: Validationsupporting
confidence: 90%
See 1 more Smart Citation
“…where is the evaporation time before correction; D0, present, the droplet diameter in this study; and D0, previous, the droplet diameter in previous studies. Figure 4 shows that the experimental results of the present study agree well with the results of previous studies near the LFP [16,27]. Comparison of evaporation time with those in previous studies [16,27].…”
Section: Validationsupporting
confidence: 90%
“…To assess the validity of this experiment, preliminary experiments were conducted under the conditions shown in Table 2 for comparison with the results of conventional studies [16,27]. Table 2 also shows the conventional experimental conditions.…”
Section: Validationmentioning
confidence: 99%
“…Indeed, although Hassebrook et al 63 reported a linear trend of the LFP versus the droplet size for the same processed surface (see Figure S12 in the Supporting Information), this might not hold for all of the micro-/nanostructures and the droplet weight could not be the dominant contribution to the LFP shift (as discussed in subsection validation (S3) in the Supporting Information). Moreover, the effect of the gravity was not considered in the physical model proposed by Kwon et al 13 The deviation of the predictions from the experimental results was attributed mainly to a dependence of the contact patch length (assumed constant for all of the structures) on the pitch between the pillars.…”
mentioning
confidence: 95%
“…The Leidenfrost temperature depends many characteristics such as the surface characteristics 9 , liquid properties 12 , drop size 13 , and impact condition 14 . Among these factors, engineering the surface characteristics has emerged as the most promising method of increasing the Leidenfrost temperature owing to its substantial tunability.…”
Section: Introductionmentioning
confidence: 99%